2021
DOI: 10.3390/recycling6040073
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of Express Analytic Hierarchy Process (EAHP) and Partial Least Squares-Structural Equations Modeling (PLS-SEM) for Sustainable Construction and Demolition Waste Management Assessment: The Case of Malaysia

Abstract: Construction and demolition waste (CDW), as the main consequence of construction and demolition (C&D) activities, has severely affected our sustainability needs. However, construction and demolition waste management (CDWM) lacks the integration of sustainability concepts. Thus, there is a great need to include sustainability dimensions in CDWM to reach sustainable construction and demolition waste management (SCDWM). This study aims at empirically investigating SCDWM by analyzing the impacts of factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 102 publications
(140 reference statements)
0
19
0
3
Order By: Relevance
“…Sustainable management of C&DW is therefore of paramount importance to mitigate and reduce the environmental impacts of C&DW. Thus, it takes into consideration reducing raw material consumption, reusing materials, appropriate recycling mechanisms, and minimizing waste generation from construction and demolition tasks [18]. Despite great previous efforts, the current practice in the construction industry is far from reaching the goals of sustainability to fully achieve sustainable construction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable management of C&DW is therefore of paramount importance to mitigate and reduce the environmental impacts of C&DW. Thus, it takes into consideration reducing raw material consumption, reusing materials, appropriate recycling mechanisms, and minimizing waste generation from construction and demolition tasks [18]. Despite great previous efforts, the current practice in the construction industry is far from reaching the goals of sustainability to fully achieve sustainable construction.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have assessed the barriers to sustainable construction and demolition waste management (C&DWM). Some studies showed that the economic concerns are the most influential in C&DWM from both governmental and institutional perspectives [18,19]. Negash et al [1] found that the eliminating regulatory and social barriers can significantly enhance the performance of C&DWM.…”
Section: Introductionmentioning
confidence: 99%
“…During the construction, renovation, and demolition phases of a project, there is an enormous consumption of raw materials, which creates a substantial amount of waste [8,9]. The quantity of construction and demolition (C&D) waste, also known as solid waste, generated from C&D activities is increasing [10], and it is increasingly threatening to the public environment and human health globally [11].…”
Section: Introductionmentioning
confidence: 99%
“…Operation Research is a field of study that uses advanced analytical methods to understand complex systems and make the right decisions [ 9 , 10 , 11 ]. Simulation techniques [ 12 , 13 , 14 , 15 ], mathematical optimisation [ 16 , 17 ], and decision analysis [ 18 ] are just a few of the ways OR helps enterprises and organisations improve their operations. OR, with its emphasis on increasing efficiency [ 19 , 20 ], cost-effectiveness [ 21 , 22 ], and decision-making [ 23 , 24 ], is particularly valuable for analysing complicated health issues, particularly in contexts where disease burden is high, but health systems are not well prepared.…”
Section: Introductionmentioning
confidence: 99%